2020
DOI: 10.1055/s-0040-1710400
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Oral Health Status, Practices, and Access to Care among War-Affected Refugees Living in San Antonio, Texas

Abstract: Objectives Refugees encounter several health disparities including oral health problems.This study evaluated the self-reported oral health status, practices, and access to care of adult refugees living in San Antonio, Texas, United States. Materials and Methods Adult refugees (n = 207) who accessed services from two centers in San Antonio, completed this survey. Multivariate logistic regression was used to examine the relationship of the refugees’ demographics with oral health status, practices, and access to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 22 publications
1
19
1
Order By: Relevance
“…The study by Salim et al [24] reported that pain was the most commonly presented disorder in 444 patients, stating that more than half of the dental treatments carried out were extractions, 74.1% of which were due to caries. Similarly, pain was a common symptom reported by participants in the research of Saadeh et al [25], and more than half of the participants reported needing dental care, but not being able to receive it given their low socioeconomic status. Research by Zinah et al [26] shows that periodontal disease and dental caries are the most frequently assessed study conditions.…”
Section: Discussionmentioning
confidence: 85%
“…The study by Salim et al [24] reported that pain was the most commonly presented disorder in 444 patients, stating that more than half of the dental treatments carried out were extractions, 74.1% of which were due to caries. Similarly, pain was a common symptom reported by participants in the research of Saadeh et al [25], and more than half of the participants reported needing dental care, but not being able to receive it given their low socioeconomic status. Research by Zinah et al [26] shows that periodontal disease and dental caries are the most frequently assessed study conditions.…”
Section: Discussionmentioning
confidence: 85%
“…Half of the studies were qualitative ( 9 , 18 , 20 , 29 , 31 , 35 ) with two interviews with refugees ( 9 , 20 ) and one being an ethnographic study ( 31 ). Two cross sectional studies ( 32 , 34 ) and two scoping review studies ( 13 , 16 ), one systematic review ( 33 ) and one documentary analysis were also included ( 19 ). Most of the studies based were conducted in Australia ( n = 4) ( 18 , 19 , 29 , 36 ) followed by the United States ( n = 2) ( 32 , 34 ) and Canada ( n = 2) ( 20 , 31 ).…”
Section: Resultsmentioning
confidence: 99%
“…Affordability significantly impacts the experiences of refugees accessing dental health services, as they often encounter challenges due to the high cost of treatments, transportation expenses, and limited financial resources ( 9 , 16 , 18 , 20 , 29 , 31 , 33 , 34 , 36 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations